Training on Utilizing Plastic Waste into Accessory Products as a Business Opportunity for Housewives in Gampong Peurada, Banda Aceh - Syarifah Farissi Hamama; Maulida Maulida; Irma Aryani; Mira Agustin; Suci Ramadhana (Universitas Lancang Kuning, 2023)
Gampong Peurada is a village located in the centre of Banda Aceh and is close to office complexes, schools, and universities. Thus, most of the buildings and housing in Gampong Peurada are used as boarding and rental houses. This has the impact of high plastic waste in the region, which is influenced by lifestyle and high consumption levels of plastic. The problem of plastic waste is a very important environmental problem. Because plastic waste is a type of waste that is very difficult to decompose, one alternative way to reduce plastic waste is to recycle it into accessory products. This process is easier, allows for honed creativity, and has become a business opportunity for housewives in Gampong Peurada. With this training, it is hoped that the community will be able to understand the management and processing of plastic waste and seize business opportunities from plastic waste to improve their welfare.